Land capability and irrigability classification of the Ganjigatti sub-watershed in the Hilly zone of Karnataka - YADAV, M. BHARGAVA NARASIMHA; PATIL, P.L. (Journal of Soil and Water Conservation, 2024)
This study was undertaken to evaluate land capability classification (LCC) and land irrigability classification (LIC) of soils representing twenty-one soil series of Ganjigatti sub-watershed of the Dharwad district in the Hilly Zone of Karnataka for sustainable land use planning. The soil series namely AKT, ASR, BGD, BGH, BNK, BTP, GJG, HNL, HRG, KDK, KMD, KRK, MLP, MRK, MVD, RMN, SDK, SGL, SSK, UGK and YSJ were mapped into sixty-one mapping units and soil map was generated using ArcGIS 10.8.2. Slope, extent of erosion, drainage, soil depth, soil texture and stoniness were considered in developing LCC. The result indicates that capability classes III and IV (86.93% of TGA) are suitable for agriculture while class VI (4.83% of TGA) is unsuitable for cultivation. The land irrigability map showed four irrigability categories (S1, S2, S3 and N1). Classes S1, S2, and S3 (55.32% of TGA) are suitable to irrigation, whereas class N1 (36.43% of TGA) is not suitable for irrigation.